Team Health and Project Quality Are Improved When Peer Evaluation Scores Affect Grades on Team Projects - ONeill, Thomas A.; Boyce, Melissa; McLarnon, Matthew J. W. (Frontiers in Education, 2020)
The use of team projects is common in higher education. Teamwork offers an avenue to help students learn to collaborate and develop the interpersonal skills needed for career success. However, the teams are not always effective, which may undermine student learning, growth, and development. In the current research, we integrate accountability, valence, motivation, and social loafing theories in order to advance an understanding of the role of peer evaluations conducted at the end of a team project. We use a state-of-the-art peer feedback system that allows students to assess and evaluate each other on five competencies critical to teamwork. This system also permits the assessment of overall team functioning. These outcomes are critical as they are related to learning as well as grades on team projects. Over three years and using a total sample size of 162 teams and 873 students, we found that the use of peer evaluations for grading purposes, compared to a control group, promoted effective team member behavior and overall team health. Future research is needed to further investigate the optimal use of peer evaluations in a variety of contexts using a variety of methods.